Unverricht-Lundborg disease (EPM1) in Finland: A nationwide population-based study - Jussi O.T. Sipilä; Jelena Hyppönen; Ville Kytö; Reetta Kälviäinen (Advanstar Communications, 2022)
To investigate the epidemiology and prognosis of Unverricht-Lundborg disease (EPM1) in a nationwide, population-based setting.
Data from multiple registries were combined and analyzed. Clinical data were obtained from medical records. All patients treated for EPM1 in Finland between January 1, 1998, and December 31, 2016 were included.
A total of 135 persons with EPM1 (54% women) were identified and 105 were alive on December 31, 2016 (point prevalence 1.91/100,000 persons). The age-standardized (European Standard Population 2013) prevalence was 1.53/100,000 persons. Annual incidence during the study period was 0.022/100,000 person-years, with a mean age at onset of 9.4 ± 2.3 years (range 7.0-14.6 years, no sex difference). The median age at death (n = 34) was 53.9 years (interquartile range 46.4, 60.3; range 23.2-63.8), with no sex differences. The immediate cause of death was a lower respiratory tract infection in 56% of deaths. The survival rates of the patients were comparable to matched controls up to 40 years of age, but poorer during long-term follow-up (cumulative survival 26.4% vs 78.0%), with a hazard ratio (HR) for death of 4.61. The risk of death decreased with increasing age at onset (HR 0.76 per year, 95% confidence interval 0.65-0.89). In approximately 10% of all cases, the disease progression appeared very mild; some patients retained functional independence for decades.
Unverricht-Lundborg disease is rare in Finland but still more common than anywhere else in the world. The disease course appears somewhat more severe than elsewhere, disability mounts early, and death occurs prematurely.